Neue Zeitschrift für Systematische Theologie und Religionsphilosophie (De Gruyter, 1959)
The journal examines the exciting dialogue between Lutheran-Reformed theology and philosophy in the broadest sense, seeks to keep open a breadth of responsible thought in the controversial issue of contemporary theology, and offers a variety of ways to formulate questions. Through its international editorial board, it guarantees an exchange of theological research in German and English.